Robot control and kinematic analysis with 6DoF manipulator using direct kinematic method - Khalaf S Gaeid; Asaad F Nashee; Ibrahim A. Ahmed; Mohammed H. Dekheel (Institute of Advanced Engineering and Science, 2021)
The robots pay important role in all parts of our life. Hence, the modeling of the robot is essential to develop the performance specification. Robot model of six degree of freedom (6DoF) manipulator implemented numerically using model-based technique. The kinematic analysis and simulation were studied with Inverse kinematics of the robot manipulator through Denevit and Hartenberg method. Matrix transformation method is used in this work in order to separate joint variables from kinematic equations. The finding of the desired configuration is obtained precisely in all motion trajectory along the end-effector path. MATLAB/SIMULINK with R2018b is used for the implementation of the model-based robot system. Simulation results showed that the robot rinks follow their references smoothly and precisely and ensure the effectiveness of direct kinematic algorithm in the analysis and control of the robotic field.